Education, Technology and Skill Premium : A Dynamic General Equilibrium Analysis - PAI, Anusha (Institutional Knowledge at Singapore Management University, 2007)
Education, Technology and Skill Premium: a Dynamic General Equilibrium Analysis is a two fold attempt to capture skill premium dynamics. First, it examines results across a cross section of model economies at different stages of economic development. It equates these model economies to real economies and compares skill premium results with the measure of income inequality. Second, it makes a valiant attempt to capture the non linear dynamics present in the US skill premium across 20th century, not captured so far in any dynamic general equilibrium model. Though the simplistic nature of the model leaves out many fine trends, the long run dynamics are well captured. The last section of the paper simulates the effect of introducing wage subsidies, on skill premium. In a setting where skill acquisition and wage earning are rival goods, it shows that a declining wage subsidy policy creates the optimal result of a sharp fall in skill premium along with a rise in the supply of educated workers. The paper serves as a base for further study, when the economy is opened to the forces of globalization.